[Cost-effectiveness analysis of delayed-release dimethyl-fumarate in the treatment of relapsing-remitting multiple sclerosis in Italy] - Gianluca Furneri; Laura Santoni; Chiara Marchesi; Sergio Iannazzo; Paolo Angelo Cortesi; Achille Patrizio Caputi; Lorenzo Giovanni Mantovani (Farmeconomia: Health Economics and Therapeutic Pathways, 2016)
INTRODUCTION: Disease Modifying Therapies (DMTs) have significantly improved clinical conditions of Relapsing Remitting Multiple Sclerosis (RRMS) patients. However, several unmet needs are still relevant in RRMS. Recently, a new therapy, delayed-release dimethyl-fumarate (DMF; also known as gastro-resistant DMF), has been approved and reimbursed by the Italian Drug Agency (AIFA) for the treatment of RRMS. OBJECTIVE: To compare the cost-effectiveness of DMF vs. pharmacological alternatives indicated for the first-line treatment of RRMS in Italy. METHODS: The analysis was conducted from the perspective of the Italian National Healthcare Service (NHS) and outcomes and costs were evaluated over a 50-year time horizon (equivalent to a lifetime horizon). Both outcomes and costs were discounted at 3.5%. The Markov model estimates the clinical and economic consequences of treating RRMS patients with the following therapeutic options: DMF, interferon (IFN) beta-1a intramuscular (IM); IFN beta-1a subcutaneous (SC) at two different doses, 22 mcg and 44 mcg; IFN beta-1b SC; glatiramer acetate (GA) SC 20 mg; oral teriflunomide. Clinical efficacy data used in this analysis came from an elaboration of the mixed treatment comparison (MTC) already published. According to the Italian NHS perspective, only the following direct costs were considered: pharmacological treatment acquisition, treatment monitoring, relapse management, direct costs associated with disability, adverse event management. Administration costs were assumed equal to €0, because every treatment included in the economic analysis can be self-administered. One-way and probabilistic sensitivity analyses were developed and cost effectiveness acceptability curves generated. RESULTS: In the base-case analysis, DMF was more efficacious than alternatives, in terms of both survival (19.496 vs. 19.297-19.461 discounted LYs, respectively), and QALYs (6.548 vs. 5.172- 6.212 discounted QALYs, respectively). Per-patient lifetime costs with DMF amounted to € 276,500, similarly to the other options. DMF was the drug with the largest effect of disability cost reduction. DMF was dominant vs. IFN beta-1a 44 mcg and cost-effective vs. all other IFNs, GA and teriflunomide, with incremental cost-effectiveness ratio (ICERs) between € 11,272 and € 23,409. All ICER values were lower than the € 50,000 per QALY threshold. One-way sensitivity analysis showed that, for all tested scenarios, ICER of DMF vs. therapeutic alternatives remained favourable (≤ 50.000 €/QALY gained) and the results of probabilistic sensitivity analysis showed that the probability for DMF of being favourable (≤ 50.000 €/QALY gained) was between around 70% and 93%, thus ensuring robustness of the results.